Inflationary Dynamics of Consumer and Producer Financing: A case of Islamic and Conventional Banking in Pakistan - Manzoor, Arslan; Arshed, Noman (Universitas Muhammadiyah Yogyakarta, 2021)
One of the macroeconomics objectives is to stabilize purchasing power for the masses, which remains a leading economic problem in Pakistan for years. Economists are convinced about some degree of inflation in the economy to mobilize economic resources, with the condition to keep it to a minimum. Currently, Islamic finance is setting its firm footing in Pakistan and competing with the conventional financial system. Under this scenario, this study compares the Shari’ah compliant financing provided by Islamic financial institutes, and human made standards of conventional financial institutions. This study explores the effect of consumer financing and producer financing of Islamic and conventional banks on the inflation of Pakistan. Quarterly secondary data between 2009Q2 to 2019Q2 extracted from the State Bank of Pakistan reports and International Financial Statistic. ARCH model is used to estimate the model. Empirical results displayed that Islamic consumer financing, as expected in theory, helps to control inflation. The preaching of moderation in Islamic finance makes Islamic consumer financing less inflationary, and asset-based Islamic producer financing will perform better in reducing inflation. Islamic consumer financing is well participating in the management of inflation. However, Islamic producer financing lacks inflation curtailing ability. The small share in the financial market, and lack of long-term investment plans, are the few reasons why Islamic producer financing is not managing inflation.